Examining the digital organizational identity through content analysis of missions and vision statements of Malaysian and Singaporean SME company websites - Abdullah, Zulhamri; Anumudu, Chinedu Eugenia; Raza, Syed Hassan (Emerald Publishing, 2022)
Purpose: This study aims to examine the current state of mission and vision statements on the company websites of fast-growing Malaysian and Singaporean small- and medium-sized enterprises (SMEs) and analyze how these attributes are functionally used to build a distinct digital organizational identity. Design/methodology/approach: The content analysis method was used to examine the similarities and differences among 170 Malaysian and Singaporean-selected SMEs based on Aaker’s five brand personality scales. Findings: The findings demonstrated that there were explicit discrepancies between Malaysian and Singaporean SMEs in the applications of brand personality attributes. The findings also identified an increase in communicating mission and vision statements on the websites of both Malaysian and Singaporean SMEs. This emphasizes the need for Malaysian and Singaporean companies to intensify their efforts to develop a notable digital organizational identity. Research limitations/implications: This study endeavors to provide novel insights into the digital communication practices of SMEs in building digital organization identity based on brand personality elements. Therefore, this study theoretically advances Aaker’s brand personality framework by incorporating digital organizational identity as a concept of Aaker’s brand personality from the SME perspective. This study contributes to the organizational identity literature by highlighting the need for these SMEs to integrate brand personality dimensions to compete with leading global companies. Practical implications: The findings indicate that managers of SMEs can develop a unique digital organizational identity by communicating their vision and mission statements on their websites as a strategic asset for sustaining corporate reputation. Originality/value: To date, little is known about the inevitable adaptation and application of communication that occurs when using digital means to develop a digital organizational identity. To the best of the authors’ knowledge, this is the first study to establish how Asian SMEs communicate their unique brand personality through websites to build their digital organizational identity.